Glass

By strictly limiting the glass composition and strain points of low-alkali glass, the problem of large heat shrinkage in the p-Si·TFT manufacturing process is solved, and the effects of reduced heat shrinkage, high productivity and good devitrification resistance are achieved.

CN115259661BActive Publication Date: 2025-04-11NIPPON ELECTRIC GLASS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210873971.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-03-07
Filing Date
2017-12-18
Publication Date
2025-04-11
Estimated Expiration
2037-12-18

AI Technical Summary

Technical Problem

The conventional glass plate has a large heat shrinkage in the manufacturing process of p-Si·TFT, resulting in a deviation of the pixel pitch of the TFT, showing poor display, and a method of reducing heat shrinkage, such as annealing treatment, which requires a long time to increase the manufacturing cost.

Method used

By strictly limiting the glass composition and strain points of low alkali glass, the specific component content is SiO2 55-70%, Al2O3 15-25%, B2O3 0-1%, Li2O+Na2O+K2O 0-0.5%, MgO 2-6%, CaO 2-8%, SrO 0-4%, BaO 6-12%, and the strain point is higher than 720°C to reduce heat shrinkage.

Benefits of technology

The heat shrinkage in the p-Si·TFT manufacturing process is achieved, which improves the productivity and devitrification resistance of the glass plate, and reduces the manufacturing cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003756258800000111
    Figure BDA0003756258800000111
  • Figure BDA0003756258800000121
    Figure BDA0003756258800000121
  • Figure BDA0003756258800000131
    Figure BDA0003756258800000131
Patent Text Reader

Abstract

The alkali-free glass of the present invention is characterized in that, as a glass composition, it contains, in mass%, SiO2 55-70%, Al2O3 15-25%, B2O3 0-1%, Li2O+Na2O+K2O 0-0.5%, MgO 2-6%, CaO 2-8%, SrO 0-4%, and BaO 6-12%, and the strain point is higher than 720°C.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the application with application number: 201780064231.0, PCT application number: PCT / JP2017 / 045254, application date: 2017.12.18, invention name: "Glass". Technical Field

[0002] The present invention relates to glass, and in particular to glass suitable for a substrate of an organic EL display. Background Art

[0003] Electronic devices such as organic EL displays are used for applications such as displays of mobile phones because they are thin, have excellent video display capabilities, and consume little power.

[0004] Glass plates are widely used as substrates for organic EL displays. The following properties are mainly required for glass plates for this purpose.

[0005] (1) In order to prevent the diffusion of alkali ions in the semiconductor material formed into a film during the heat treatment step, the content of the alkali metal oxide is small.

[0006] (2) To reduce the cost of glass sheets, the glass sheets have excellent productivity, and in particular, excellent resistance to devitrification and melting properties.

[0007] (3) In the manufacturing process of p-Si·TFT, the strain point is high in order to reduce thermal shrinkage.

[0008] (4) In order to reduce the self-weight deflection during the transportation process, it is higher than the Young's modulus.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application No. 2009-525942 Summary of the invention

[0012] Problems to be solved by the invention

[0013] If (3) above is described in detail, there is a heat treatment process at 400 to 600°C in the manufacturing process of p-Si TFT, and in the above heat treatment process, the glass plate undergoes a small dimensional change called thermal shrinkage. If the thermal shrinkage is large, the pixel pitch of the TFT will deviate, which will become a cause of poor display. In the case of an organic EL display, even a dimensional shrinkage of a few ppm may cause poor display, and a glass plate with low thermal shrinkage is required. It should be noted that the higher the heat treatment temperature to which the glass plate is subjected, the greater the thermal shrinkage.

[0014] As a method of reducing the thermal shrinkage of a glass sheet, there is a method of performing an annealing treatment near the slow cooling point after forming the glass sheet. However, the annealing treatment requires a long time, so the production cost of the glass sheet increases.

[0015] As another method, there is a method of increasing the strain point of the glass plate. The higher the strain point, the less likely it is to cause thermal shrinkage in the manufacturing process of p-Si·TFT. For example, Patent Document 1 discloses a glass plate with a high strain point. However, if the strain point is high, productivity is likely to decrease.

[0016] The present invention has been made in view of the above circumstances, and a technical object of the present invention is to produce glass which has excellent productivity (particularly resistance to devitrification), a high specific Young's modulus, and a small thermal shrinkage in the manufacturing process of p-Si·TFT.

[0017] Means for solving problems

[0018] The inventors of the present invention have repeatedly conducted various experiments and found that the above-mentioned technical problems can be solved by strictly limiting the glass composition and strain point of low-alkali glass, and thus proposed the present invention. That is, the glass of the present invention is characterized in that, as a glass composition, it contains SiO2 55-70%, Al2O3 15-25%, B2O3 0-1%, Li2O+Na2O+K2O 0-0.5%, MgO 2-6%, CaO 2-8%, SrO 0-4%, BaO 6-12%, and the strain point is higher than 720°C. Here, "Li2O+Na2O+K2O" refers to the total amount of Li2O, Na2O and K2O. "Strain point" refers to the value measured by the method based on ASTM C336.

[0019] Second, the glass of the present invention preferably has a mass % ratio SiO2 / Al2O3 of 3.6 or less. Here, "SiO2 / Al2O3" refers to the value obtained by dividing the content of SiO2 by the content of Al2O3.

[0020] Third, the glass of the present invention preferably contains, in terms of mass%, SiO2 57-65%, Al2O3 18-22%, B2O3 0% or more and less than 1%, Li2O+Na2O+K2O 0% or more and less than 0.1%, MgO 2-4%, CaO 3-7%, SrO 0-3%, and BaO 7-11%.

[0021] Fourthly, the glass of the present invention preferably has a mass % ratio of MgO / CaO of 0.5 to 0.9. Here, "MgO / CaO" refers to a value obtained by dividing the content of MgO by the content of CaO.

[0022] Fifthly, the glass of the present invention preferably contains 17.0 to 19.1% by mass of MgO+CaO+SrO+BaO(RO). Here, "MgO+CaO+SrO+BaO" refers to the total content of MgO, CaO, SrO, and BaO, that is, the total amount of alkaline earth metal oxides.

[0023] Sixth, the glass of the present invention preferably has a mass % ratio (MgO+CaO+SrO+BaO) / Al2O3 of 0.94 to 1.13. Here, "(MgO+CaO+SrO+BaO) / Al2O3" refers to the value obtained by dividing the total content of MgO, CaO, SrO, and BaO by the content of Al2O3.

[0024] Seventh, the glass of the present invention preferably has a mol% ratio of SiO2 / Al2O3 of 5.4 to 5.9.

[0025] Eighth, the glass of the present invention preferably further contains 0.001 to 1 mass % of SnO2.

[0026] Ninth, the glass of the present invention preferably has a Young's modulus, that is, a value obtained by dividing the Young's modulus by the density, greater than 29.5 GPa / g·cm -3 .

[0027] Tenth, the glass of the present invention preferably has a high temperature viscosity of 10 2.5 dPa·s is 1695°C or lower. Here, “high temperature viscosity 10 2.5 The "surface temperature" can be measured using the platinum ball pulling method.

[0028] Eleventh, the glass of the present invention preferably has a liquidus temperature of less than 1300° C. Here, the “liquidus temperature” can be calculated by placing glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains at 50 mesh (300 μm) into a platinum boat, keeping it in a temperature gradient furnace for 24 hours, and measuring the temperature at which crystals are precipitated.

[0029] Twelfth, the glass of the present invention preferably has a viscosity of 10 4.8 Here, the "viscosity at the liquidus temperature" can be measured by a platinum ball pulling method.

[0030] Thirteenth, the glass of the present invention is preferably in a flat plate shape and has an overflow confluence surface at the center in the plate thickness direction. That is, the glass of the present invention is preferably formed by an overflow down-draw method.

[0031] Fourteenthly, the glass of the present invention is preferably used in an organic EL device. DETAILED DESCRIPTION

[0032] The glass of the present invention is characterized in that, as a glass composition, it contains SiO2 55-70%, Al2O3 15-25%, B2O3 0-1%, Li2O+Na2O+K2O 0-0.5%, MgO 2-6%, CaO 2-8%, SrO 0-4%, and BaO 6-12%. The reasons for limiting the content of each component as described above are shown below. It should be noted that, in the description of the content of each component, unless otherwise specified, the expression of % means mass %.

[0033] SiO2 is a component that forms the glass skeleton and increases the strain point. The content of SiO2 is 55-70%, preferably 58-65%, and especially 59-62%. If the content of SiO2 is small, the strain point and acid resistance are likely to decrease, and the density is likely to increase. On the other hand, if the content of SiO2 is large, the high-temperature viscosity increases, the solubility is likely to decrease, and in addition, the balance of the glass components is destroyed, devitrified crystals such as cristobalite are likely to precipitate, and the liquidus temperature is likely to increase. Furthermore, the etching rate based on HF is likely to decrease.

[0034] Al2O3 is a component that increases the strain point and the Young's modulus. The content of Al2O3 is 15-25%, preferably 17-23%, 18-22%, 18.2-21%, and especially 18.6-21%. If the content of Al2O3 is small, the strain point and the specific Young's modulus are likely to decrease. On the other hand, if the content of Al2O3 is high, the devitrified crystals of mullite and feldspar are likely to precipitate, and the liquidus temperature is likely to increase.

[0035] SiO2 / Al2O3 is an important component ratio for taking into account high strain point, devitrification resistance and solubility at a high level. The two components have the effect of increasing the strain point as described above, but if the amount of SiO2 becomes relatively large, devitrified crystals such as cristobalite are easily precipitated, and solubility is easily reduced. On the other hand, if the amount of Al2O3 becomes relatively large, devitrified crystals of alkaline earth aluminosilicates such as mullite and anorthite are easily precipitated. Therefore, the mass % ratio SiO2 / Al2O3 is preferably 2.5-4, 2.6-3.6, 2.8-3.3, and especially 3.1-3.3. In addition, the mole % ratio SiO2 / Al2O3 is preferably 4.9-6.5, 5.2-6.0, and especially 5.4-5.9.

[0036] B2O3 is a component that improves solubility and resistance to devitrification. The content of B2O3 is 0-1%, preferably 0.1% or more and less than 1%, 0.3-0.75%, and especially 0.5-0.7%. If the content of B2O3 is small, the solubility is likely to decrease, and the liquidus temperature is likely to increase. In addition, the resistance to buffered hydrofluoric acid (BHF resistance) is likely to decrease. On the other hand, if the content of B2O3 is high, the strain point, acid resistance, and specific Young's modulus are likely to decrease. In addition, it is easy to mix water into the glass from the raw material for introducing B2O3, and the β-OH value is likely to increase. Furthermore, in the case of wanting to increase the strain point as much as possible, the content of B2O3 is preferably 0% or more and less than 1%, 0% or more and less than 0.1%, and especially 0% or more and less than 0.07%.

[0037] Li2O, Na2O and K2O are components that improve the meltability and reduce the resistivity of the molten glass. However, if a large amount of Li2O, Na2O and K2O are contained, there is a possibility that the semiconductor material will be contaminated by the diffusion of alkali ions. Therefore, the content of Li2O+Na2O+K2O is 0 to 0.5%, preferably 0.01 to 0.3%, 0.02 to 0.2%, and especially 0.03% or more and less than 0.1%. In addition, the content of Na2O is preferably 0 to 0.3%, 0.01 to 0.3%, 0.02 to 0.2%, and especially 0.03% or more and less than 0.1%.

[0038] MgO is a component that improves meltability and Young's modulus. The content of MgO is 2 to 6%, preferably 2 to 5%, 2.5 to 4.5%, and particularly 3 to 4%. If the content of MgO is low, it is difficult to ensure rigidity and meltability is easily reduced. On the other hand, if the content of MgO is high, mullite or devitrified crystals derived from Mg and Ba and devitrified crystals of cristobalite are likely to precipitate, and the strain point is significantly reduced.

[0039] CaO is a component that reduces high-temperature viscosity and significantly improves solubility without lowering the strain point. In addition, CaO is a component that reduces the cost of raw materials in alkaline earth metal oxides by introducing relatively cheap raw materials. It is also a component that increases Young's modulus. Moreover, CaO has the effect of inhibiting the precipitation of the above-mentioned Mg-containing devitrified crystals. The content of CaO is 2 to 8%, preferably 3 to 7%, 3.5 to 6%, and especially 3.5 to 5.5%. If the content of CaO is small, it is difficult to enjoy the above-mentioned effect. On the other hand, if the content of CaO is high, the devitrified crystals of calcium feldspar are easy to precipitate and the density is easy to increase.

[0040] The mass % ratio MgO / CaO is an important component ratio for achieving both high devitrification resistance and high specific Young's modulus. If the mass % ratio MgO / CaO is small, the specific Young's modulus is likely to decrease. On the other hand, if the mass % ratio MgO / CaO is large, the liquidus temperature is likely to rise due to devitrification crystals containing Mg. Therefore, the mass % ratio MgO / CaO is preferably 0.4 to 1.5, 0.5 to 1.0, 0.5 to 0.9, and particularly 0.6 to 0.8.

[0041] SrO is a component that suppresses phase separation and improves resistance to devitrification. It is also a component that reduces high-temperature viscosity and improves solubility without lowering the strain point. On the other hand, if the SrO content is high, in a glass system such as the present invention that contains a large amount of CaO, feldspar-based devitrification crystals are likely to precipitate, and resistance to devitrification is likely to decrease. There is also a tendency for density to increase or Young's modulus to decrease. Therefore, the SrO content is 0 to 4%, preferably 0 to 3%, 0 to 2%, 0 to 1.5%, 0 to 1%, and especially 0% or more and less than 1%. On the other hand, by replacing with BaO, the decrease in Young's modulus is suppressed and the increase in density can be further suppressed. In the case of wanting to obtain such an effect, the SrO content is preferably 1 to 4%, 2 to 4%, and especially 3 to 4%.

[0042] BaO is a component that has a high effect of inhibiting the precipitation of mullite-based and anorthite-based devitrified crystals among alkaline earth metal oxides. The content of BaO is 6 to 12%, preferably 7 to 11%, 8 to 10.7%, and especially 9 to 10.5%. If the content of BaO is small, mullite-based and anorthite-based devitrified crystals are easily precipitated. On the other hand, if the content of BaO is large, the density increases, or the Young's modulus is easily reduced, and the high-temperature viscosity becomes too high, and the solubility is easily reduced.

[0043] Alkaline earth metal oxides are very important components for increasing the strain point, devitrification resistance, and solubility. If there are few alkaline earth metal oxides, the strain point rises, but it is difficult to suppress the precipitation of devitrification crystals of the Al2O3 system, and the high-temperature viscosity becomes high, and the solubility is easily reduced. On the other hand, if there are many alkaline earth metal oxides, the solubility is improved, but the strain point is easily reduced, and there is a possibility of a decrease in liquid phase viscosity caused by a decrease in high-temperature viscosity. Therefore, the content of MgO+CaO+SrO+BaO is preferably 16-20%, 17-20%, 17.0-19.5%, and especially 18-19.3%.

[0044] The mass % ratio (MgO+CaO+SrO+BaO) / Al2O3 is an important component ratio for suppressing the precipitation of various devitrified crystals and lowering the liquidus temperature. If the mass % ratio (MgO+CaO+SrO+BaO) / Al2O3 becomes smaller, the liquidus temperature of mullite tends to become higher. On the other hand, if the mass % ratio (MgO+CaO+SrO+BaO) / Al2O3 becomes larger, the alkaline earth metal oxides become more, and the feldspar-based or alkaline earth metal-containing devitrified crystals tend to precipitate. Therefore, the mass % ratio (MgO+CaO+SrO+BaO) / Al2O3 is preferably 0.80 to 1.20, 0.84 to 1.15, 0.94 to 1.13, and especially 0.94 to 1.05.

[0045] In addition to the above-mentioned components, for example, the following components may be added.

[0046] ZnO is a component that improves solubility, but if a large amount of ZnO is contained, the glass is likely to devitrify and the strain point is likely to decrease. Therefore, the ZnO content is preferably 0 to 5%, 0 to 3%, 0 to 0.5%, and particularly 0 to 0.2%.

[0047] P2O5 is a component that increases the strain point, but if a large amount of P2O5 is contained, the glass is prone to phase separation. Therefore, the content of P2O5 is preferably 0 to 1.5%, 0 to 1.2%, and particularly preferably 0% or more and less than 0.1%.

[0048] TiO2 is a component that reduces high temperature viscosity, improves melting properties, and inhibits exposure to sunlight. However, if a large amount of TiO2 is contained, the glass is easily colored and the transmittance is easily reduced. Therefore, the content of TiO2 is preferably 0-5%, 0-3%, 0-1%, 0-0.1%, and especially 0-0.02%.

[0049] ZrO2, Y2O3, Nb2O5, and La2O3 have the effect of increasing the strain point and Young's modulus. However, if the content of these components is high, the density tends to increase. Therefore, the content of ZrO2, Y2O3, Nb2O5, and La2O3 is preferably 0-5%, 0-3%, 0-1%, 0% or more and less than 0.1%, and especially 0% or more and less than 0.05%, respectively. In addition, the total amount of Y2O3 and La2O3 is preferably less than 0.1%.

[0050] SnO2 is a component that has a good clarification effect in the high temperature region, and is a component that increases the strain point and reduces the high temperature viscosity. The content of SnO2 is preferably 0-1%, 0.001-1%, 0.01-0.5%, and especially 0.05-0.3%. If the content of SnO2 is high, devitrified crystals of SnO2 are easily precipitated. Furthermore, if the content of SnO2 is low, it is difficult to enjoy the above effects.

[0051] As long as the glass properties are not impaired, F2, Cl2, SO3, C or metal powder such as Al, Si, etc. can be added up to 5% as a clarifier. In addition, CeO2, etc. can be added up to 1% as a clarifier.

[0052] As2O3 and Sb2O3 are effective as clarifiers, and the glass of the present invention does not completely exclude the introduction of these components, but from an environmental point of view, it is preferred not to use these components as much as possible. In addition, if As2O3 is contained in a large amount in the glass, there is a tendency for the light resistance to decrease, so its content is preferably 0.1% or less, and it is desirable that it is substantially free of As2O3. Here, "substantially free of As2O3" refers to the case where the content of As2O3 in the glass composition is less than 0.05%. In addition, the content of Sb2O3 is preferably 0.2% or less, especially 0.1% or less, and it is desirable that it is substantially free of Sb2O3. Here, "substantially free of Sb2O3" refers to the case where the content of Sb2O3 in the glass composition is less than 0.05%.

[0053] Fe2O3 is a component that reduces the resistivity of molten glass. The content of Fe2O3 is preferably 0.001-0.1%, 0.005-0.05%, and especially 0.008-0.015%. If the content of Fe2O3 is small, it is difficult to enjoy the above-mentioned effect. On the other hand, if the content of Fe2O3 is large, the transmittance in the ultraviolet region is easy to decrease, and the irradiation efficiency when using the laser in the ultraviolet region in the process of the display is easy to decrease. Furthermore, in the case of electric melting, it is preferred to actively introduce Fe2O3, in which case, the content of Fe2O3 is preferably 0.005-0.03%, 0.008-0.025%, and especially 0.01-0.02%. In addition, in the case of wanting to increase the transmittance in the ultraviolet region, the content of Fe2O3 is preferably 0.020% or less, 0.015% or less, 0.011% or less, and especially 0.010% or less.

[0054] Cl has the effect of promoting the melting of low-alkali glass. If Cl is added, the melting temperature can be lowered and the effect of the clarifier can be promoted. In addition, it has the effect of reducing the β-OH value of the molten glass. However, if the Cl content is too much, the strain point is easily reduced. Therefore, the Cl content is preferably 0.5% or less, especially 0.001 to 0.2%. Furthermore, as the introduction raw material of Cl, chlorides of alkaline earth metal oxides such as strontium chloride, or raw materials such as aluminum chloride can be used.

[0055] The glass of the present invention preferably has the following glass properties.

[0056] In the glass of the present invention, the strain point exceeds 720° C., preferably 730° C. or higher, 740° C. or higher, and particularly 750 to 850° C. If the strain point is low, the glass plate is easily thermally shrunk during the manufacturing process of p-Si·TFT.

[0057] The density is preferably 2.68 g / cm 3 Below, 2.66g / cm 3 Below, 2.65g / cm 3 Below, especially 2.64g / cm 3 If the density is high, the specific Young's modulus becomes high, and the glass is easily bent due to its own weight.

[0058] The average thermal expansion coefficient in the temperature range of 30 to 380°C is preferably 34×10 -7 / ~43×10 -7 / ℃, especially 38×10 -7 / ~41×10 -7 / ℃. If the average thermal expansion coefficient in the temperature range of 30 to 380℃ is outside the above range, it will not match the thermal expansion coefficient of the surrounding components, which will easily cause the surrounding components to peel off and the glass plate to warp. Here, "the average thermal expansion coefficient in the temperature range of 30 to 380℃" refers to the value measured by a dilatometer.

[0059] The HF etching rate is preferably 0.8 μm / min or more, 0.9 μm / min or more, and particularly 1 μm / min or more. If the HF etching rate is low, it is difficult to thin the glass plate in the slimming process. Here, the "HF etching rate" refers to a value calculated from the etching depth when etching is performed using a 5 mass % HF aqueous solution at 20° C. for 30 minutes after a portion of the mirror-polished glass surface is shielded using a polyimide tape.

[0060] The liquidus temperature is preferably less than 1300° C., 1280° C. or lower, 1260° C. or lower, and particularly preferably 1240° C. or lower. If the liquidus temperature is high, devitrified crystals are generated during forming by the overflow down-draw method or the like, and productivity of the glass sheet is likely to decrease.

[0061] The viscosity at liquidus temperature is preferably 10 4.2 dPa·s or more, 10 4.4 dPa·s or more, 10 4.6 dPa·s or more, 10 4.8 dPa·s or more, especially 10 5.0 If the viscosity at the liquidus temperature is low, devitrified crystals are generated during forming by an overflow down-draw method or the like, and the productivity of the glass sheet is likely to decrease.

[0062] High temperature viscosity 10 2.5 The temperature at dPa·s is preferably 1695°C or less, 1660°C or less, 1640°C or less, 1630°C or less, and particularly 1500 to 1620°C. 2.5 As the temperature in dPa·s increases, it becomes difficult to melt the glass, and the production cost of the glass sheet increases.

[0063] The specific Young's modulus is preferably more than 29.5 GPa / g·cm -3 、30GPa / g·cm -3 Above, 30.5GPa / g·cm -3 Above, 31GPa / g·cm -3 Above, 31.5GPa / g·cm -3 Above, especially 32 GPa / g·cm -3 If it is higher than the Young's modulus, the glass plate is easily bent due to its own weight.

[0064] In the glass of the present invention, if the β-OH value is reduced, the strain point can be increased. The β-OH value is preferably 0.30 / mm or less, 0.25 / mm or less, 0.20 / mm or less, 0.15 / mm or less, and especially 0.10 / mm or less. If the β-OH value is too large, the strain point is easily reduced. Furthermore, if the β-OH value is too small, the meltability is easily reduced. Therefore, the β-OH value is preferably 0.01 / mm or more, especially 0.05 / mm or more.

[0065] The following methods can be cited as methods for reducing the β-OH value. (1) Selecting raw materials with low water content. (2) Adding components that reduce the amount of water in the glass (such as Cl and SO3). (3) Reducing the amount of water in the furnace environment. (4) Bubbling N2 in the molten glass. (5) Using a small melting furnace. (6) Increasing the flow rate of the molten glass. (7) Using the electric melting method.

[0066] Here, the "β-OH value" refers to a value obtained by measuring the transmittance of glass using FT-IR and using the following formula.

[0067] β-OH value = (1 / X)log(T1 / T2)

[0068] X: Glass wall thickness (mm)

[0069] T1: Reference wavelength 3846cm -1 Transmittance under

[0070] T2: Hydroxyl absorption wavelength 3600cm -1 Minimum transmittance near (%)

[0071] The glass of the present invention is preferably in a flat plate shape and has an overflow confluence surface in the central part of the plate thickness direction. That is, it is preferably formed by an overflow down-draw method. The so-called overflow down-draw method refers to a method in which molten glass is overflowed from both sides of a wedge-shaped refractory material, the overflowed molten glass is converged at the lower end of the wedge, and is extended downward to be formed into a flat plate shape. In the overflow down-draw method, the surface that should become the surface of the glass plate does not contact the refractory material, but is formed in a free surface state. Therefore, a glass plate that is not ground and has good surface quality can be manufactured cheaply, and it is also easy to enlarge the area and thin the wall.

[0072] In addition to the overflow down-draw method, a glass sheet can be formed by, for example, a slot down-draw method, a re-draw method, a float method, or a roll pressing method.

[0073] In the glass of the present invention, the wall thickness (the plate thickness in the case of a flat plate shape) is not particularly limited, and is preferably 1.0 mm or less, 0.7 mm or less, 0.5 mm or less, and particularly 0.4 mm or less. The smaller the plate thickness, the easier it is to make the organic EL device lightweight. It should be noted that the wall thickness can be adjusted by the flow rate or the plate pulling speed during glass manufacturing.

[0074] The method for industrially manufacturing the glass of the present invention is a method for manufacturing a glass plate, preferably comprising: a melting step of putting the prepared glass batch into a melting furnace and heating the mixture by electric current using a heating electrode to obtain a molten glass; and a forming step of forming the obtained molten glass into a flat plate-shaped glass having a plate thickness of 0.1 to 0.7 mm by an overflow down-draw method. The glass plate contains, as a glass composition, SiO2 55 to 70%, Al2O3 15 to 25%, B2O3 0 to 1%, Li2O+Na2O+K2O 0 to 0.5%, MgO 2 to 6%, CaO 2 to 8%, SrO 0 to 4%, BaO 6 to 12%, and has a strain point higher than 720°C.

[0075] The manufacturing process of glass sheets generally includes a melting process, a clarification process, a supply process, a stirring process, and a forming process. The melting process is a process of melting a glass batch material prepared by mixing glass raw materials to obtain molten glass. The clarification process is a process of clarifying the molten glass obtained in the melting process by using a clarifier or the like. The supply process is a process of transporting the molten glass between the processes. The stirring process is a process of stirring and homogenizing the molten glass. The forming process is a process of forming the molten glass into a flat plate-shaped glass. Furthermore, as required, processes other than the above, such as a state adjustment process for adjusting the molten glass to a state suitable for forming, may be incorporated after the stirring process.

[0076] In the case of manufacturing existing low-alkali glass in industry, it is usually melted by heating the combustion flame of a burner. The burner is usually arranged above the melting kiln, and as fuel, fossil fuels are used, specifically liquid fuels such as heavy oil, gaseous fuels such as LPG, etc. The combustion flame can be obtained by mixing fossil fuels with oxygen. However, in this method, a large amount of water is mixed in the molten glass during melting, so the β-OH value is easy to rise. Therefore, when manufacturing the glass of the present invention, it is preferably carried out by energizing heating using a heating electrode, preferably not by heating the combustion flame of a burner, but by energizing heating using a heating electrode to melt. Thus, it is difficult for moisture to be mixed into the molten glass during melting, so it is easy to define the β-OH value as less than 0.30 / mm, less than 0.25 / mm, less than 0.20 / mm, less than 0.15 / mm, and especially less than 0.10 / mm. In addition, if energizing heating using a heating electrode is carried out, the energy used to obtain the molten glass per unit mass is reduced, and the molten volatiles decrease, so the environmental load can be reduced.

[0077] The heating by the electric conduction of the heating electrode is preferably carried out by applying an alternating voltage to the heating electrode arranged at the bottom or side of the melting furnace so as to contact the molten glass in the melting furnace. The material used in the heating electrode is preferably a material having heat resistance and corrosion resistance to the molten glass, for example, tin oxide, molybdenum, platinum, rhodium, etc. can be used, and molybdenum is particularly preferred from the viewpoint of the degree of freedom of installation in the furnace.

[0078] The glass of the present invention has a high resistivity because the content of alkali metal oxide is small. Therefore, when the low-alkali glass is heated by the electric heating electrode, not only the molten glass but also the refractory constituting the melting furnace flows with current, and there is a possibility that the refractory constituting the melting furnace is damaged in advance. In order to prevent the above situation, it is preferred to use a zirconia-based refractory with high resistivity, especially a zirconia electrocasting refractory brick, as the refractory in the furnace, and it is also preferred to introduce a small amount of components (Li2O, Na2O, K2O, Fe2O3, etc.) that reduce the resistivity in the molten glass (glass composition), and it is particularly preferred to introduce a small amount of Li2O, Na2O, K2O, etc. In addition, the content of Fe2O3 is preferably 0.005-0.03 mass%, 0.008-0.025 mass%, especially 0.01-0.02 mass%. In addition, the content of ZrO2 in the zirconia-based refractory is preferably 85 mass% or more, especially 90 mass% or more.

[0079] Example

[0080] The present invention will be described below based on examples.

[0081] Tables 1 to 3 show examples of the present invention (sample Nos. 1 to 50). In addition, "NA" in the table means not measured.

[0082] [Table 1]

[0083]

[0084] [Table 2]

[0085]

[0086] [Table 3]

[0087]

[0088] First, add the glass batch material prepared by mixing the glass raw materials in a manner to obtain the glass composition in the table into a platinum crucible and melt it at 1600-1650°C for 24 hours. When the glass batch material is melted, stir it with a platinum stirrer to homogenize it. Then, let the molten glass flow onto a carbon plate, form it into a plate, and then slowly cool it for 30 minutes at a temperature near the slow cooling point. For each sample obtained, the average thermal expansion coefficient α, density (Density), β-OH value, HF etching rate (HF etching rate), strain point Ps, annealing point Ta, softening point Ts, high temperature viscosity 10 4.5 Temperature at dPa·s, high temperature viscosity 10 4.0 Temperature at dPa·s, high temperature viscosity 10 3.0 Temperature at dPa·s, high temperature viscosity 10 2.5 The temperature at dPa·s, the liquidus temperature TL and the liquidus viscosity logη at TL, Young's modulus and specific Young's modulus.

[0089] The average thermal expansion coefficient α in the temperature range of 30 to 380° C. is a value measured using a dilatometer.

[0090] The density is a value measured by the known Archimedean method.

[0091] The β-OH value is a value measured by the above-mentioned method.

[0092] The HF etching rate is a value calculated from the etching depth when a part of the mirror-polished glass surface is masked with a polyimide tape and then etching is performed with a 10 mass % HF aqueous solution at 20° C. for 30 minutes.

[0093] The strain point Ps, annealing point Ta, and softening point Ts are values ​​measured according to the methods of ASTM C336 and C338.

[0094] High temperature viscosity 10 4.5 dPa·s, 10 4.0 dPa·s, 10 3.0 dPa·s and 10 2.5 The temperature in dPa·s is a value measured by a platinum ball pulling method.

[0095] The liquidus temperature TL is obtained by placing glass powder that passes through a standard sieve of 30 mesh (pore size 500 μm) but remains in a 50 mesh (pore size 300 μm) sieve into a platinum boat, keeping it in a temperature gradient furnace for 24 hours, and measuring the precipitation temperature of crystals (primary phase).

[0096] Liquid viscosity log 10 ηTL is a value obtained by measuring the viscosity of glass at the liquidus temperature TL using a platinum ball pulling method.

[0097] The Young's modulus is a value measured using a known resonance method. The specific Young's modulus is a value obtained by dividing the Young's modulus by the density.

[0098] As can be seen from Tables 1 to 3, the contents of alkali metal oxides in Samples No. 1 to 50 are small, the strain points are above 738°C, and the high temperature viscosity is 10 2.5 The temperature at dPa·s is below 1693°C, the liquidus temperature is below 1281°C, and the viscosity at the liquidus temperature is 10 4.50 dPa·s or more, specific Young's modulus is 30.4GPa / g·cm -3 Therefore, it is considered that Sample Nos. 1 to 50 can be suitably used as a substrate for an organic EL display.

Claims

1. A glass, characterized in that: The glass composition includes, by mass%, SiO2 55% to 70%, Al2O3 18.6% to 25%, B2O3 0.3% to 1%, Li2O+Na2O+K2O 0% to 0.5%, MgO 2% to 6%, CaO 2% to 8%, SrO 0% to 4%, BaO6% to 12%, P2O5 0% or more and less than 0.1%, and the strain point is higher than 720°C.

2. The glass according to claim 1, characterized in that The mass % ratio SiO2 / Al2O3 is less than 3.

6.

3. The glass according to claim 1 or 2, characterized in that: As for the glass composition, it contains, by mass%, SiO2 57% to 65%, Al2O3 18.6% to 22%, B2O3 0.3% or more and less than 1%, Li2O+Na2O+K2O 0% or more and less than 0.1%, MgO 2% to 4%, CaO 3% to 7%, SrO 0% to 3%, BaO 7% to 11%, and P2O 50% or more and less than 0.1%.

4. The glass according to claim 1 or 2, characterized in that: The mass % ratio MgO / CaO is 0.5 to 0.

9.

5. The glass according to claim 1 or 2, characterized in that: The content of MgO+CaO+SrO+BaO is 17.0 mass % to 19.1 mass %.

6. The glass according to claim 1 or 2, characterized in that: The mass % ratio (MgO+CaO+SrO+BaO) / Al2O3 is 0.94~1.

13.

7. The glass according to claim 1 or 2, characterized in that: The molar % ratio SiO2 / Al2O3 is 5.4 to 5.

9.

8. The glass according to claim 1 or 2, characterized in that: It also contains 0.001 mass % to 1 mass % of SnO2.

9. The glass according to claim 1 or 2, characterized in that: Specific Young's modulus greater than 29.5 GPa / g·cm -3 .

10. The glass according to claim 1 or 2, characterized in that: High temperature viscosity 10 2.5 The temperature at dPa·s is 1695°C or less.

11. The glass according to claim 1 or 2, characterized in that: The liquidus temperature is below 1300°C.

12. The glass according to claim 1 or 2, characterized in that: The viscosity at liquidus temperature is 10 4.8 dPa·s or above.

13. The glass according to claim 1 or 2, characterized in that: It is in the shape of a flat plate and has an overflow confluence surface at the center in the plate thickness direction.

14. The glass according to claim 1 or 2, characterized in that: Used in organic EL devices.

Citation Information

Patent Citations

  • Glass composition with high thermal and chemical stability and method for producing the same

    JP2009525942A

  • Alkali-free glass

    CN103201228A

  • Non-alkali glass

    CN105452182A

  • Glass compositions with high thermal and chemical stability

    JP2014503465A

  • Glass with improved total pitch stability

    JP2016505502A